A Unique B-Family DNA Polymerase Facilitating Error-Prone DNA Damage Tolerance in Crenarchaeota - Feng, Xu; Liu, Xiaotong; Xu, Ruyi; Zhao, Ruiliang; Feng, Wenqian; Liao, Jianglan; Han, Wenyuan; She, Qunxin (Frontiers in Microbiology, 2020)
Sulfolobus islandicus codes for four DNA polymerases: three of the B-family (Dpo1, Dpo2 and Dpo3) and one of the Y-family (Dpo4). Western analysis revealed that, among the four polymerases, only Dpo2 exerted DNA damage-inducible expression. To investigate how Dpo2 as well as other DNA polymerases could contribute to DNA damage tolerance, we conducted genetic analysis of their encoding genes in Sulfolobus islandicus. Plasmid-borne gene expression revealed that Dpo2 facilitates cell survival upon DNA damage at the expense of mutagenesis. Gene deletion experiments showed, while dpo1 is essential, the remaining three genes are dispensable. Furthermore, while Dpo4 functions in house-keeping translesion DNA synthesis, Dpo2, a B-family DNA polymerase once predicted inactive, is solely responsible for the targeted mutagenesis. Mutation spectrum analysis revealed that Dpo2 mainly facilitates GC to AT/TA conversions upon DNA damage. Together, our data indicates that Dpo2 is the main DNA polymerase responsible for DNA damage tolerance and is the primary source of mutagenesis. Given crenarchaea encoding a Dpo2 also have a low-GC composition, the Dpo2-dependent DNA repair pathway may be conserved in this archaeal lineage.